Kinematic and kinetic differences between ball rotational exercises and the throwing motion in collegiate baseball athletes - Mylott, J. A.; Potts, E. M.; Wolf, J. H.; Bullock, G. S.; Nicholson, K. F. (The Journal of Strength and Conditioning Research, 2024)
The purpose of this study was to observe the associations that medicine ball pushes and chops have on the lower extremities regarding ground reaction forces (GRF) and lead knee flexion angles and to compare these values with a regular baseball overhead throw. Lower extremity kinetics and kinematics were obtained via force plates and marker motion capture. Subjects (n = 35) included baseball players (age 19.7 ± 1.5 years). Five medicine ball movements of each type along with at least 3 pitches or 5 throws off the mound were recorded for data collection. Statistical parametric mapping, including analysis of variance and 2-way t-tests, was used to compare the variables of interest between the movements for continuous time data. All kinematic and kinetic variables were significantly different (p < 0.05) for some time during the motion between the different trial types of medicine ball exercises and throws. A medicine ball chop can increase peak drive leg GRF, whereas a push can help an athlete keep greater driver leg GRF and maintain ground connection into foot plant. A push helps train lead leg deficiencies in the delivery. Both the medicine ball chop and push have benefits for training lead leg stabilization and extension.